Circulating insulin and leptin in women with and without premenstrual disphoric disorder in the menstrual cycle. (May 2013) - Akturk, Mujde; Toruner, Fusun; Aslan, Selcuk; Altinova, Alev E.; Cakir, Nuri; Elbeg, Sehri; Arslan, Metin
Abstract Premenstrual dysphoric disorder (PMDD) is a syndrome related with mood and appetite changes during the late luteal phase. Leptin and insulin are the hormones related to appetite, and leptin may have a role in reproductive functions and mood. Our aim was to determine whether there are differences in serum leptin and insulin levels between women with and without PMDD during the follicular and luteal phases. In this study, 20 women with PMDD and 18 women without PMDD were included. Fasting blood glucose, insulin, leptin, progesterone levels and HOMA-IR were measured in the follicular and luteal phases separately. Repeated-measures analysis of variance revealed significant interactions for serum leptin, insulin and HOMA-IR levels between the diagnosis of PMDD and menstrual phases (F = 5.4, p = 0.025; F = 5.4, p = 0.026; and F = 4.7, p = 0.036, respectively). A significant correlation was found between progesterone and insulin levels in subjects without PMDD in the luteal phase (r = 0.58, p = 0.01). Whether the alterations in serum leptin and insulin are related with the changes of appetite and mood in PMDD or secondary to other factors should be clarified.